Stability of native starch quality parameters, starch extraction, and root dry matter of cassava genotypes in different environments - Benesi, I.R.M.; Labuschagne, Maryke T.; Dixon, Alfred G.O.; Mahungu, N.M. (Wiley, 2004)
Cassava is an important food and cash crop in Malawi. It is also becoming increasingly important for industrial use. The aim of this study was to investigate the native starch quality of different Malawi cassava genotypes. Trials were conducted at Chitedze and Makoka in Malawi in the 2000/01 season. Apart from root dry matter and starch extraction, starch quality parameters considered included protein, moisture and ash contents, pH and whiteness. Various stability measures were used to deal with the problem of genotype × environment interaction. The results showed that all the cassava genotypes produced starch with no protein and with colour as white as required by the industry. Moisture and ash contents and pH fell within the industry‐recommended ranges. This suggests that native cassava starch is suitable for use in various industries. Additive main effects and multiplicative interaction (AMMI) was strongly correlated with other measured stability parameters and is therefore recommended for stability analysis of starch quality parameters. Genotype had a larger influence than environment on root dry matter. This agrees with the hypothesis that one or a few major genes control root dry matter in cassava.